The study of the effect of the individual perception of justice (belief in a just world) on degree of decision-making of students of the faculty of physical education and sport sciences - Buket Kayaoglu; Gökhan Acar; Gulsum Yılmaz; Rezzan Demırcı (Türk Spor ve Egzersiz Dergisi)
This study aims to reveal the research results of the effects of the relation between individual perception of justice (belief in a just world) and decision-making on the students of faculty of physical education and sport sciences. In this context, what is the degree of individual perception of just world of the students? What is the degree of the students’ self-esteem? What are students’ decision making styles? Does students’ individual perception of justice, degree of self-esteem at decision-making and decision-making styles show difference in terms of their demographic features? Is there a significant relationship between students’ individual perception of just world, and their self-esteem at decision-making and decision-making styles? These are the questions that are investigated. In order to determine between students’ individual perception of a just world and decision-making styles, arithmetic mean and standard deviation values are examined. T test and one-way ANOVAs test are applied to determine whether students’ individual perception of a just world and decision-making styles change according to their demographic features. The mean of the answers to the questions about students’ individual perception of just world is calculated as 3.73. Students’ individual perception of a just world is quite close to 4 (neutral value). According to this, it seems that students’ individual perception of a just world is at the degree of indecision. The value of the mean of the first six items that the students’ degree of self-esteem is determined is 2.52 which is the degree of accurate. According to that, we can say that students’ degree of self-esteem at decision-making is high. The mean of the answers that the students gave to the questions about decision-making delay is 1.91 which is at the degree of sometimes accurate. According to that, we can say that students sometimes delay their decision-making process. When we compare students’ individual perception of just world, and their self-esteem at decision-making and decision-making styles in terms of their demographic features, it is seen that there is not a significant difference between the groups according to variables of gender, the grade they are in, their department they study and the dwelling place. It is seen that there is a significant difference only according to the variables of degree of doing sports and the habitual residence.